Safety Nets, Health Crises and Natural Disasters : Lessons from Sierra Leone - Sandford, Judith; Rajput, Sumati; Coll-Black, Sarah; Kargbo, Abu (World Bank, Washington, DC, 2020)
This case study suggests how shock-responsive social protection systems can be the basis of a government-led response to a health crisis and a rapid-onset disaster. It also points to how linking pre-arranged finance to safety nets can help with quick delivery of cash to vulnerable populations post-disasters. This experience complements existing evidence and experience in other parts of Africa, where social protection systems have been used for responding to drought, a slow-onset natural disaster. It also informed the ongoing response to the COVID-19 pandemic in Sierra Leone, which will provide further lessons for shock-responsive social protection globally.